Take Advantage of Tourism Development Opportunities Through Hybrid Business Activities in Indonesia - iputu artaya; Sri Wiwoho Mudjanarko; Achmad Muchayan; Made Kamisutara; Muhammad Roesli (The Spirit of Society Journal: International Journal of Society Development and Engagement, 2022)
This research was conducted in three cities that have the highest number of hybrid entrepreneurs in Indonesia. The approach in this research is to prioritize primary data by looking for facts in the field related to hybrid entrepreneurial activities. The total number of business owners is 73 people spread across Surabaya, Malang, and Denpasar. Where these entrepreneurs have managed to run their business well in a hybrid way for approximately six years. Based on the research we did, we found that there were four main factors supporting their success in running a hybrid entrepreneurship, that is digital promotion, product identity and legality, resource strength, market analysis capabilities. Based on associative analysis and testing, it is proven that these four variables have a significant influence on hybrid entrepreneurial activities. The limitation of our research is that it does not include a wider range of forms or types of variables. It only involves four variables whose strength has been recognized by entrepreneurs in the three cities. The implications of this research activity will be to be able to provide a clear picture of the development of hybrid business activities and what aspects should be considered for someone when they want to start a hybrid entrepreneur. There has never been and there are not many references to research activities that specifically discuss and examine hybrid entrepreneurial activities.